2006
DOI: 10.1080/03009740600556126
|View full text |Cite
|
Sign up to set email alerts
|

Linear scleroderma ‘en coup de sabre’ associated with cerebral and ocular vasculitis

Abstract: Linear scleroderma 'en coup de sabre' (LSCS) has been reported in association with intracranial abnormalities. We report the case of an 11-year-old boy with LSCS who presented with recurrent headaches. Cranial magnetic resonance imaging (MRI) and angiography were consistent with the diagnosis of a cerebral vasculitis. In addition, retinal examination showed an exudative inflammatory lesion consistent with vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 7 publications
1
16
0
9
Order By: Relevance
“…The reported alterations, as in our study, may involve adnexa structures,3 the anterior or posterior segments of the eye4 6 7 and the CNS 5 810. The involvement of the extrinsic eye muscles, as in one of our patients (no.19), is extremely rare but well described by both CT and MRI4 13 and should be suspected in presence of pain on eye movement, diplopia and strabismus.…”
Section: Discussionsupporting
confidence: 61%
“…The reported alterations, as in our study, may involve adnexa structures,3 the anterior or posterior segments of the eye4 6 7 and the CNS 5 810. The involvement of the extrinsic eye muscles, as in one of our patients (no.19), is extremely rare but well described by both CT and MRI4 13 and should be suspected in presence of pain on eye movement, diplopia and strabismus.…”
Section: Discussionsupporting
confidence: 61%
“…30,31,32,33 Os achados imagenológicos (RNM, SPECT) incluem atrofia ou calcificações corticais. Análise liquórica é compatível com inflamação intracerebral (Figura 3).…”
Section: 29unclassified
“…153,161 There have been case reports in which corticosteroids, methotrexate and mycophenolate mofetil effectively treated recurrent headaches and cranial nerve lesions. 142,143,162,163 There have also been reports indicating that anticonvulsants and antidepressants effectively mitigated symptoms. 144,164,165 One case report indicated that corticosteroids and azathioprine were ineffective for treating optic papillitis.…”
mentioning
confidence: 99%
“…145 One case of cerebral vasculitis, which improved with mycophenolate, has been reported. 162 Based on the above information, antiepileptic drugs are effective for treating mild epileptic seizures that are caused by brain lesions, while combined systemic steroid therapy and immunosuppressants is considered to be effective for moderate or worse epilepsy, including generalized tonic clonic seizures or treatment-resistant epileptic seizures. The evidence level on antiepileptic drugs is low, but the recommendation level is set as 1D, based on the consensus of the committee that created this guideline.…”
mentioning
confidence: 99%